What shapes cognitions of climate change in Europe? Ideology, morality and the role of educational attainment - Heinz Welsch (University of Oldenburg, Department of Economics, 2021)
Cognitions about climate change are of critical importance for climate change mitigation as they influence climate-relevant behaviors and the support of climate policy. Using about 30,000 observations from a large-scale representative survey from 23 European countries, this study provides two major findings. First, important policy-relevant climate change cognitions do not only differ by individuals' ideological identity (left versus right) but - independently - by their moral identity, that is, the pattern of endorsement of the moral foundations: Care, Fairness, Liberty, Loyalty, Authority and Purity/Sanctity. In particular, controlling for ideological position the cognitions that the world climate is changing, that climate change is human-made, and that climate change impacts are bad are significantly negatively related to stronger endorsement of the Authority and Sanctity foundations while being positively related to stronger endorsement of the Loyalty and Fairness foundations. Second, not only the ideology-related cognitive divide but the morality-related divide is larger in individuals with tertiary education, consistent with the idea that individuals with greater science literacy and numeracy use these skills to adjust their cognitions to their group identity. The finding that better education may amplify rather than attenuate the ideology and morality dependence of decision-relevant climate change cognitions sheds doubt on the proposition that better education unambiguously furthers the prospects for climate change mitigation.
Keywords: 330; climate change cognition; identity-protective cognition; ideological identity; moral identity; moral foundations; educational attainment